Diagnosing Mycobacterium Kansasii in Shoulder Periprosthetic Joint Infection: A Rare Case Report - Dmitriy Peresada; Nirav Mungalpara; Abhi Deshpande; Michael Patetta; Benjamin Goldberg (Journal of Orthopaedic Case Reports)
Introduction: Periprosthetic joint infections (PJIs) of the shoulder complicate approximately 0.7% of primary and 15.4% of revision shoulder arthroplasties. Culture-negative PJIs constitute 5–42% of cases, with fungal and mycobacterial pathogens frequently implicated, often following broad-spectrum antibiotics administration prior to tissue sampling. Mycobacteria are isolated in 43% of culture-negative PJIs and associated with advanced age, chronic steroid therapy, immunosuppression, and retroviral infections. Improved diagnostic techniques have increased the isolation and reporting of non-tuberculous mycobacteria. Mycobacterium kansasii infections in native joints and bursae are documented, but only two cases of M. kansasii PJI, both in knee PJI, are reported. This report presents the first case of a shoulder PJI caused by M. kansasii. Case Report: A 66-year-old female underwent right reverse total shoulder arthroplasty for glenohumeral osteoarthritis in November 2015. Post-operative recovery was initially uneventful, but 7 months later, she experienced persistent shoulder pain following a fall. Imaging confirmed proper component placement without loosening. In April 2017, extensive workup yielded negative results, including erythrocyte sedimentation rate and C-reactive protein. The patient returned in November 2018 with exacerbated pain, swelling, night sweats, and chills. Blood tests suggested no overt inflammation, but X-rays raised concerns of glenoid component loosening. January 2019 surgery revealed extensive synovitis and necrosis; a vancomycin and tobramycin-impregnated spacer was placed. Cultures identified M. kansasii, and the patient was treated with rifampin, azithromycin, and ethambutol for 12 months. Persistent pain led to multiple surgeries, with cultures confirming no infection. In January 2021, after consultation, long-term antimycobacterial therapy was initiated due to presumed recurrence. By June 2021, the patient reported no pain, and radiographs confirmed well-aligned prosthetic components. Conclusion: M. kansasii PJI, though rare, requires distinct diagnostic and treatment approaches compared to common pathogens. Diagnosis is often delayed due to the organism’s slow growth and culture time, necessitating advanced techniques such as polymerase chain reaction and next-generation sequencing. Effective treatment involves extended antimycobacterial therapy and multiple surgeries. This case underscores the importance of monitoring for mycobacterial growth in suspected culture-negative PJIs and employing aggressive surgical and medical therapy to minimize complications.